Factors related to long-lasting insecticidal net (LLIN) use during travel in western Kenya: A descriptive analysis. Issue 47 (May 2022) - Anderson, Elizabeth J.; Coalson, Jenna E.; Agawo, Maurice; Munga, Stephen; Hayden, Mary; Santos, Ellen M.; Little, Ashley C.; Tamari, Noriko; Ernst, Kacey
Abstract: Background: Overnight travel predicts increased likelihood of Plasmodium infection and may introduce parasite strains to new areas, but deviations from routine at-home use of long-lasting insecticidal nets (LLINs) during travel are not well studied. Methods: Cross-sectional data were taken in 2015 from the western Kenyan highlands and lowlands. Household surveys assessed individual travel activity during the previous month, LLIN use (at home and away), and current Plasmodium infection status. Crude and adjusted logistic regression was used to estimate the odds ratios (OR) of current malaria infection relative to travel within the last month. Results: Highland residents who had traveled were more likely to have Plasmodium infection at the time of interview than highland residents who had not traveled (adjusted OR = 4.09 [1.60, 10.52]). Alternately, in the lowlands those who traveled overnight were significantly less likely to be infected vs non-travelers (adjusted OR = 0.56 [0.39, 0.96]). Rates of LLIN use during travel were lower than reported rates while at home. Despite this, among travelers, LLIN use during travel was not associated with likelihood of Plasmodium infection for either region. Conclusions: Travel had heterogeneous associations with infection status for the lowlands and highlands of western Kenya. Given the higher prevalence of malaria in the lowlands, travel is unlikely to increase likelihood of exposure. Conversely, travel from the lower-prevalence highlands may have taken respondents to higher prevalence areas. LLIN use while traveling differed from at-home habits and may depend on availability of LLINs where the traveler sleeps.